Optimization of modified clean fractionation of prairie cordgrass - Cybulska, Iwona; Lei, Hanwu; Julson, James; Brudecki, Grzegorz (International Journal of Agricultural and Biological Engineering, 2012)
Iwona Cybulska1, Hanwu Lei2*, James Julson1, Grzegorz Brudecki1 (1. Department of Agricultural and Biosystems Engineering, South Dakota State University, Brookings, South Dakota 57007 USA; 2. Bioproducts, Sciences and Engineering Laboratory, Department of Biological Systems Engineering, Washington State University, Richland, Washington 99352 USA) Abstract: In this study, modified clean fractionation process was optimized for prairie cordgrass, with usage of alternative organic constituent